Detection of SPM and IMP metallo-β-lactamases in clinical specimens of Pseudomonas aeruginosa from a Brazilian public tertiary hospital - Camargo, Carlos Henrique [UNESP]; Bruder-Nascimento, Ariane [UNESP]; Mondelli, Alessandro Lia [UNESP]; Montelli, Augusto Cezar [UNESP]; Sadatsune, Terue [UNESP] (My University, 2011)
Phenotypic and genotypic SPM and IMP metallo-β-lactamases (MBL) detection and also the determination of minimal inhibitory concentrations (MIC) to imipenem, meropenem and ceftazidime were evaluated in 47 multidrug-resistant Pseudomonas aeruginosa isolates from clinical specimens. Polymerase chain reaction detected 14 positive samples to either blaSPM or blaIMP genes, while the best phenotypic assay (ceftazidime substrate and mercaptopropionic acid inhibitor) detected 13 of these samples. Imipenem, meropenem and ceftazidime MICs were higher for MBL positive compared to MBL negative isolates. We describe here the SPM and IMP MBL findings in clinical specimens of P. aeruginosa from the University Hospital of Botucatu Medical School, São Paulo, Brazil, that reinforce local studies showing the high spreading of blaSPM and blaIMP genes among Brazilian clinical isolates. © 2011 Elsevier Editora Ltda.
Keywords: Carbapenems; Drug resistance, bacterial; Metalloproteins; Polymerase chain reaction; Pseudomonas aeruginosa; ceftazidime; imipenem; imipenemase metallo beta lactamase; mercaptopropionic acid; meropenem; metallo beta lactamase; polymyxin B; propionic acid derivative; Sao Paulo metallo beta lactamase; unclassified drug; antibiotic sensitivity; bacterial gene; bacterial transmission; bacterium isolate; bla IMP gene; bla SPM gene; blood culture; body fluid; Brazil; controlled study; enzyme analysis; genotype; minimum inhibitory concentration; multidrug resistance; nonhuman; phenotype; polymerase chain reaction; sensitivity and specificity; tertiary health care; test strip; university hospital; urine culture; Anti-Bacterial Agents; beta-Lactamases; Ceftazidime; Cross Infection; Genes, Bacterial; Genotype; Hospitals, Public; Humans; Imipenem; Microbial Sensitivity Tests; Phenotype; Polymerase Chain Reaction; Thienamycins